Set-up of a novel in vitro neurocardiac cell model for the in-depth study of heart disease. (10th June 2022) - Cattelan, G; Frommelt, LS; De Bortoli, M; Mackova, K; Ciucci, G; Zacchigna, S; Pramstaller, PP; Pichler, I; Zanon, A; Rossini, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Regional Development Fund and Interreg V-A Italy-Austria 2014-2020 and the Department of Innovation, Research and University of the Autonomous Province of Bolzano-South Tyrol (Italy). Background: The autonomic nervous system (ANS) regulates the heart rate, conduction velocity, force of contraction, myocyte cohesion and relaxation of the heart [1]. The elucidation of how ANS and the heart interact and cooperate is at the basis of the comprehension of the mechanisms that participate in the development of many cardiac disorders including long QT and Brugada syndrome, ventricular tachyarrhythmia and arrhythmogenic cardiomyopathy [1]. However, the mechanisms of neuronal control of cardiac disease are still poorly characterized due to a lack of proper human cellular models. Purpose: The aim of this work is to develop an in vitro neurocardiac model using sympathetic neurons (SNs) and cardiomyocytes (CMs) both derived from human induced pluripotent stem cells (iPSCs). Methods: Commercial iPSCs were differentiated into SNs [2] and cardiomyocytes [3] using established protocols. Molecular and electrophysiological characterization of the generated cell populations was performed by qPCR, Western blot, flow cytometry, immunofluorescence and multielectrode array (MEA) analyses. Silicon-based two-well inserts with a defined cell-free gap were used for iPSC-derived SNs and CMs co-culture. SNs and CMs at approximately 30 days of differentiation were transferred in the two separated, matrigel-coated, wells of the silicon inserts, and cultured in a medium consisting of 1:1 of neural and cardiomyocyte medium. Results: iPSC-derived CMs expressed typical cardiac markers such as α-actinin, troponin I and myosin heavy chain 7 and displayed spontaneous beating activity. iPSC-derived SNs were positive for pan-neuronal (TH) and sympathetic markers (PHOX2B, DBH). iPSC-derived SNs and CMs were separately cultured as monolayers (7x10^4 cells per chamber) for 3-5 days in the two chambers of the silicon inserts. After insert removal, neuronal axons sprouted towards the cardiomyocytes, forming connection in 3-5 days. The immunofluorescence staining of the neurocardiac co-culture displayed TH-positive axonal prolongation, punctuated varicosities and the presence of synaptic vesicles positive for the neuronal phosphoprotein Synapsin-I, indicating pre-synaptic cell contacts. Preliminary functional experiments performed using a MEA device seem to indicate an increase in the beat rate of iPSC-derived CMs after 14 days of co-culture with SNs (day 0: 44.26 beats per minute (bpm ); day 14: 87.61 bmp). This increase was not visible in monocultures of iPSC-derived CMs. Conclusions: The establishment of this co-culture methodology and the preliminary observations collected in this work provide a promising in vitro cell model for a deeper investigation of the neurocardiac interconnection and future insights for drug screening and modelling of many cardiac disorders.